Rationalism And Islamic Thought: A Comparative Study Of Rene Descartes And Harun Nasution On The Position Of Ratio - Sumanto, Edi (Yayasan Darussalam Bengkulu, 2025)
This study examines the comparative perspectives of René Descartes and Harun Nasution on the role of reason (ratio) in the pursuit of truth. Using a library research approach with qualitative descriptive analysis, this study investigates how Descartes elevates reason as the primary source of knowledge through his rationalist philosophy, Harun Nasution underscores the integration of reason and revelation within Islamic intellectual tradition. In contrast, the study highlights that Descartes, through the notion of cogito ergo sum (“I think, therefore I am”), regards reason as the ultimate foundation of certainty, independent of sensory perception or divine revelation. In contrast, Harun Nasution emphasizes that reason holds a high position in Islam but must be aligned with revelation, especially in understanding theology and religious practice. This comparative analysis highlights the importance of reason in both Western rationalism and modernist Islamic thought, while also illustrating their distinct epistemological approaches. This study contributes to contemporary debates on the role of rationality in religion and philosophy, particularly in the context of Islamic education and modern philosophy.